2021
DOI: 10.1016/j.jtumed.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy, accountability, and competition: The privatisation of the Saudi health care system

Abstract: Objectives This study aims to explore the perceptions of different stakeholders about the privatisation of the Saudi health care system. Methods Using a qualitative case study design, we interviewed 21 administrators and clinical staff of a public hospital in the Eastern Province of the KSA and analysed all official documents relevant to this study. The analysis followed a thematic approach to provide an in-depth interpretation of the data. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…The newly introduced concepts of privatization and PPPs in Saudi Arabia has limited qualitative data available and once such study explored the perceptions of different stakeholders regarding the privatization of the Saudi health care system by interviewing administrators and clinical staff of the public hospital in the Eastern province of Kingdom. 8 The study findings suggests that the privatization is perceived as an opportunity that introduces the missing role of competition with the private sector, however carefully points-out that a better comprehension of the implementation process and new dynamics determining the Saudi health care system is required. 8 …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The newly introduced concepts of privatization and PPPs in Saudi Arabia has limited qualitative data available and once such study explored the perceptions of different stakeholders regarding the privatization of the Saudi health care system by interviewing administrators and clinical staff of the public hospital in the Eastern province of Kingdom. 8 The study findings suggests that the privatization is perceived as an opportunity that introduces the missing role of competition with the private sector, however carefully points-out that a better comprehension of the implementation process and new dynamics determining the Saudi health care system is required. 8 …”
Section: Discussionmentioning
confidence: 88%
“… 8 The study findings suggests that the privatization is perceived as an opportunity that introduces the missing role of competition with the private sector, however carefully points-out that a better comprehension of the implementation process and new dynamics determining the Saudi health care system is required. 8 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…RThe majority of the interviewees (16/27) stated that the relationship between the stakeholders is being improved with the adoption of new strategies and implementation of innovative technologies. However, recent studies 42 , 43 have revealed various factors influencing stakeholder relationships. Significant influence of government regulations, competitors, suppliers, patients, the public, and health service providers, was identified in developing the Saudi health care system, which can be addressed by creating awareness among stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“… 42 In addition, changes in the governance structure, gradually increased autonomy from the government, lack of accountability in hospitals, and cooperative relationships between cluster hospitals were identified. 43 Though the importance of digital health services is realized for improving relationships between stakeholders, there are few issues as identified from the above studies affecting the process of relationship management. These factors might further affect the delivery of health care services, which in turn affects the usability and the relationship of care providers with citizens.…”
Section: Resultsmentioning
confidence: 99%